Austerity in Time of Crisis: A Solution or a Dangerous Idea? Evidence from Algeria - Hadjer Boulila; Mohamed Benbouziane (Faculty of Economic and Business, 2018)
Our study is aimed to investigate the effect of austerity measures on the economic growth. Besides that, this research wants to examine whether austerity is the solution of the current oil crisis in Algeria or not. To achieve this aim we have used a Non-Linear Autoregressive Lag Distributed model (NARDL) to illustrate the negative and positive changes in austerity measures and their effects on gross domestic product. The findings of our estimation provides that neither increasing taxes cuts nor reducing expenditures is a solution for the crisis, that what confirms empirically what Keynesian economists approve. Therefore, Algeria’s authorities must quickly find other solution rather than austerity policies.DOI: 10.15408/etk.v17i1.6799